Britannica student encyclopedia an A to Z encyclopedia. (Gale virtual reference library, 2015)
This updated set helps children gain a better understanding of their world. It includes more than 2,250 articles, covering everything from Barack Obama to video games. Provides help for elementary and middle school children to gain a better understanding of their world and assist in homework help, and assignments. Features 2,700 photos, charts, and tables that help explain concepts and subjects, as well as 1,200 maps and flags from across the globe.